What Matters for C4 Transporters: Evolutionary Changes of Phosphoenolpyruvate Transporter for C4 Photosynthesis - Lyu, Ming-Ju Amy; Wang, Yaling; Jiang, Jianjun; Liu, Xinyu; Chen, Genyun; Zhu, Xin-Guang (Frontiers in Plant Science, 2020)
C4 photosynthesis is a complex trait, which evolved from its ancestral C3 photosynthesis by recruiting pre-existing genes. These C4 co-opted genes were changed in many aspects compared to their counterparts in C3 species. Most of the evolutionary changes of the C4 shuttle enzymes are well characterized, however, evolutionary changes for the recruited metabolite transporters are largely unknown. Here we analyzed the evolutionary changes of phosphoenolpyruvate (PEP) transporter (PPT) during its recruitment from C3 to C4 photosynthesis. Our analysis showed that among the two PPT paralogs, i.e. PPT1 and PPT2, PPT1 was the copy recruited to C4 photosynthesis in multiple C4 lineages. During C4 evolution, PPT1 gained increased transcript abundance, shifted its expression from predominantly in root to in leaf, from bundle sheath cell to mesophyll cell, and gained more rapid and long-lasting responses to light. Modifications in both regulatory and coding regions were observed, however, the original function of PPT were remained. The case study of PPT suggested that high transcript abundance in a proper location is of high priority for PPT to support C4 function.